2016
DOI: 10.1038/ncomms10351
|View full text |Cite
|
Sign up to set email alerts
|

Functional anterior pituitary generated in self-organizing culture of human embryonic stem cells

Abstract: Anterior pituitary is critical for endocrine systems. Its hormonal responses to positive and negative regulators are indispensable for homeostasis. For this reason, generating human anterior pituitary tissue that retains regulatory hormonal control in vitro is an important step for the development of cell transplantation therapy for pituitary diseases. Here we achieve this by recapitulating mouse pituitary development using human embryonic stem cells. We find that anterior pituitary self-forms in vitro followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(149 citation statements)
references
References 37 publications
(55 reference statements)
4
140
0
Order By: Relevance
“…Together, SHH signaling is essential for pituitary specification by driving the earliest stages of pituitary development and regulating the early progenitor cells. In agreement, development of pituitary-phenotypical cells from pluripotent stem cells invariably requires activation of the SHH pathway (Suga et al 2011, Dincer et al 2013, Ozone et al 2016, Zimmer et al 2016.…”
Section: Sonic Hedgehog: Regulator Of Adult Pituitary Stem Cell Prolimentioning
confidence: 82%
“…Together, SHH signaling is essential for pituitary specification by driving the earliest stages of pituitary development and regulating the early progenitor cells. In agreement, development of pituitary-phenotypical cells from pluripotent stem cells invariably requires activation of the SHH pathway (Suga et al 2011, Dincer et al 2013, Ozone et al 2016, Zimmer et al 2016.…”
Section: Sonic Hedgehog: Regulator Of Adult Pituitary Stem Cell Prolimentioning
confidence: 82%
“…There are currently several published studies in which hPSCs are differentiated into organoids of various tissues including stomach [119], intestine [120–122], liver [46, 123, 124], lung [125], brain [126], anterior pituitary [127], and kidneys [3, 6, 7, 19, 51]. Here, we summarize four studies that generated kidney organoids from hPSCs (Key Figure, Figure 3, and Figure 4).…”
Section: Comparison Of Kidney Organoid Differentiation Protocolsmentioning
confidence: 99%
“…Recent studies demonstrated a derivation of anterior pituitary hormone-producing cells from human embryonic or induced pluripotent stem cells, which are able to function in response to stimulus in murine hypopituitarism models [8, 12], with the two-dimensional approach by Zimmer et al [12] generating functional cells at higher efficiency. In order for in vitro-generated cells to achieve homeostatic control in vivo, these have to be grafted within the pituitary or in immediate contact with the hypothalamus [13-16].…”
Section: Generation Of Pituitary Endocrine Cells From Pluripotent Stementioning
confidence: 99%